Determination of radon source in basaltic groundwater, using geochemical tracers and chemometric statistical analysis - Jim Stanley; Lucy Reading (Heliyon)
Geochemical tracers such as stable isotopes are widely used in groundwater studies for determining aquifer connectivity and groundwater-surface water interactions. An analysis of dissolved radon (222Rn), major ions and trace element chemistry in groundwater was conducted in the fractured-rock aquifer system of Springbrook plateau, southeast Queensland, Australia. Chemical tracers were used to explore hydrological connectivity between the basalt formation and the underlying rhyolite formation. Water samples were collected from groundwater bores installed in both rock formations, from August 2021 to November 2023. Analysis revealed higher than expected concentrations of radon present in groundwater extracted from the basaltic aquifers (>20 Bq/L). A geochemical analysis of rock samples collected from the plateau, combined with a statistical analysis of water sample chemistry, confirmed the rhyolite formation as the primary source of radon. This indicates a strong hydrological connectivity between the rhyolite and basalt formations, such that the dissolved radon gas in groundwater is easily able to migrate through the network of fractures from the rhyolite formation into the overlying basalt formation. There are indications that seasonal rainfall events may be an important factor controlling the extent of vertical groundwater movement, as shown by temporal changes in radon concentrations. Hence, the groundwater aquifers in both formations should not be considered as discrete, disconnected systems. The geochemical tracers in both water and rock samples used in this investigation, combined with a chemometric statistical analysis, proved to be useful for identifying inter-aquifer connectivity in an area with no previous groundwater investigations.